A new conventional regression model to estimate hourly photosynthetic photon flux density under all sky conditions. (29th March 2017) - Foyo‐Moreno, I.; Alados, I.; Alados‐Arboledas, L.
ABSTRACT: In this work, we propose a new and simple empirical model to estimate photosynthetic photon flux density under all sky conditions, developed using experimental measurements carried out at Granada, an urban site in Southeastern Spain during 2 recent years (2014–2015). The model uses the solar zenith angle and clearness index as input parameters, and thus needs only global irradiance measurements usually registered in most radiometric networks. Five stations located in the Northern and Southern Hemispheres with different climatological characteristics at Europe, Asia and America (Spain, Japan and Argentina) were used to validate the model. The model provides satisfactory results, with low mean bias error (MBE) for all stations, particularly MBE, being less than 1% in absolute values in three stations and root mean square error below 6% for all stations except one with 6.1%. These results show better accuracy in comparison with other earlier empirical models and suggest the effectiveness of the model by its general applicability.